ANALISIS BEBAN KERJA PRODUKSI MEJA EASY FOLDING DENGAN METODE FULL TIME EQUIVALENT (FTE) (STUDI KASUS DI CV QIRANA FACTORY JEPARA) (Science and Technology (SciTech), 2023)
CV Qirana Factory Jepara is one of the furniture companies in Jepara city. The raw material used for production is a type of teak wood. This company produces various types of furniture including, tables, chairs, benches, and sunbeds. The purpose of this study is to determine the standard time of easy folding table production and the workload received by easy folding table manufacturing operators. In this study using the measurement of working time stop hours (Stopwatch Time Study) with the Full Time Equivalent (FTE) workload calculation method. The data that has been obtained is then processed data uniformity test, data adequacy test, adjustment factor, normal time calculation, determining the allowance time, raw time calculation, then calculating the workload using the Full Time Equivalent (FTE) method. After calculation, the standard time for the production of one easy folding table was 424.59 minutes or 7 hours 7 minutes. As for the calculation of CV Qirana Factory Jepara's easy folding table production workload, the materialization operator workload is 240% overload, the foot frame manufacturing operator workload is 155% overload, the table top operator manufacturing workload is 67% underload, the assembly operator workload The table is 109% normal, the sanding operator workload is 46% underload, and the finishing operator workload is 58% % underload. Work overload with FTE value > 1.28, normal workload with FTE value between , 1-1.28 and underload workload with FTE value between 0-0.99.